James Bryce’s Role in the Armenian Question - Fahriye Begüm Yıldızeli (Tarih Dergisi)
With the implementation of cultural imperialist policies during the reign of Queen Victoria, which is described as the most glorious era in the history of Great Britain, one of the main targets of the British aristocrats was the Christian minorities in the Ottoman Empire. Irish academician, diplomat, and politician James Bryce is one of the important propagandists who helped to create public opinion on the Armenian Question and Turkish hostility. In addition to his efforts to ensure that England was active in the Armenian Question since the 1870s, he founded the Anglo-Armenian Association in 1893. Bryce, who aimed to strengthen the so-called Armenian massacre allegations at the request of the British Government in 1915, is an important actor who contributed to the systematic advancement of propaganda activities by publishing the work called Blue Book with the historian Arnold J. Toynbee. James Bryce’s versatile political identity, who has been interested in history, law, and diplomacy throughout his 84 years of life, has made him one of the leading authorities of the Liberal Party. In addition to his political career, Bryce tried to keep the psychological dynamics of the British policy on the Armenian Question on the agenda. This study will analyse Bryce’s thoughts on bringing the Armenian Question to the international level and evaluate the effects of his political communication activities on the British and American public.